Immediate modulation effects of Tongue Tri-needle on brain functional networks in infratentorial stroke patients with dysphagia: a randomized controlled trial - Sun, Fang; Huang, Xiaoyan; Qiao, Jia; Wang, Lian; Cheng, Xue; Chen, Yan (Frontiers in Neurology, 2025)
BackgroundTongue Tri-needle has demonstrated clinical efficacy in post-stroke dysphagia, but its neuromodulatory mechanisms in infratentorial stroke patients remain unclear. This study aimed to investigate the characteristics of resting-state brain functional networks in infratentorial stroke patients with dysphagia and the dynamic modulation of brain functional networks induced by Tongue Tri-needle.MethodsThirty eligible infratentorial stroke patients with dysphagia were randomly assigned to either the Tongue Tri-needle group or sham needle group. Functional near-infrared spectroscopy (fNIRS) was used to monitor brain activity across four experimental states. Graph theory analysis quantified changes in brain network functional connectivity (FC) and topological properties, complemented by clinical swallow function assessments.ResultsBaseline analyses showed reduced functional connectivity between the fronto-temporo-parietal regions and the primary sensorimotor cortex, with the degree of reduction correlating with clinical impairment. Acupuncture specifically enhanced FC between frontal and temporal–parietal cortices, strengthened interhemispheric sensorimotor cortex connectivity, and significantly increased network centrality in the right dorsal lateral prefrontal cortex (DLPFC). During the electroacupuncture phase, frontotemporal-sensorimotor connections were further strengthened, whereas the post-needle resting state revealed adaptive reorganization of the network.ConclusionInfratentorial stroke patients with dysphagia exhibit disrupted functional connectivity within the fronto-temporo-sensorimotor network, which is associated with clinical impairment. Tongue Tri-needle multi-stage, selective reconfiguration of brain functional networks, particularly by modulating the right DLPFC, a key hub, to promote functional integration of swallow-related neural networks. These findings provide a neuromodulatory mechanism supporting the use of Tongue Tri-needle for post-stroke dysphagia.